If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + x(x) = 169 Multiply x * x 25 + x2 = 169 Solving 25 + x2 = 169 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + x2 = 169 + -25 Combine like terms: 25 + -25 = 0 0 + x2 = 169 + -25 x2 = 169 + -25 Combine like terms: 169 + -25 = 144 x2 = 144 Simplifying x2 = 144 Take the square root of each side: x = {-12, 12}
| -35=d-28 | | 2x^2+8x-309=0 | | -5(0.1x+0.4)-1.1=-0.1 | | -18=-360 | | (4v+1)(4v-1)= | | 50x+10=40 | | -54=-9f | | 5x+2(x+1)=2(2x-1) | | 72=12(n) | | -10+(2+3z)ifz=-3 | | y+18=-21 | | 72=12xn | | 3x-(-6)=30 | | log(x+6)=log(2x+5) | | 7z+8-5z=22-5z | | 5(14-2)2/2= | | m-5.99=6.4 | | 25=5/9(f-32) | | -81=n-61 | | x+27=-4 | | -12=2+r | | ln(x+6)=ln(2x+5) | | 99k*85=21l | | 18x=26+5x | | 12.99j-20.50=163.39 | | -5x=21 | | p-20=5 | | 12.1+x-7.2=5.3 | | klo+369-p*8w-44q=65 | | 7x-75=77-x | | (6x^2y^2)(9x^2y^3)= | | 7b^2+11b=-4 |